Assessing Gender Dimorphism Indicators in Anthropometric Characteristics and Features of the Bony Pelvis of Female Representatives of Pair and Group Types in Sports Acrobatics - Nataliia Veronika Bachynska; Eduard Doroshenko; Andrii Svatiev; Victor Bohuslavskyi (Physical Education Theory and Methodology)
Objectives. The study aimed to examine individual anthropometric indicators, focusing on the bony pelvis size in female acrobats of various roles during the puberty and youth age, as well as in persons who do not engage in playing sports.